Una mirada a la vida y muerte de tres inmigrantes chinos de mediados y finales del siglo XIX: análisis osteobiográfico y del ritual funerario - Phan, Julio (2021)
In 2018, three burials of Chinese immigrants from the late 19th and early 20th centuries were discovered in the Carabayllo district of Lima, during the archaeological monitoring of the private company Cálidda. This note presents the reconstruction of these funerary contexts, as well as the osteobiographies of each of these individuals, in order to get a closer look to the life, death and mortuary rituals of these persons.